Development of universal qiblat finder (UQF) using digital compass and global positioning system (GPS) - Ibrahim, Mohd Zamri; Muhammad, Badaruddin; Ramli, Mohd Syakirin; Reza Ezuan, Samin; Zuridan, Daud (2008)
People nowadays love to travel around the world. Regardless of their location and time, they especially Muslims still need to perform their five times prayer. Normally for travelers, they need to bring maps, compass and for Muslim, they even have to bring Qibla pointer when they travel. It is slightly difficult to determine the Qibla direction and to know the time for each prayer. In past, people normally used stick and by measuring its shadow, they can determine the prayer time as well as the Qibla direction. Nowadays, researches and findings in astronomical have provided much help in computing the prayer time and the direction of Qibla. A designed prototype called as Universal Qibla Finder or UQF is to locate the Qibla direction and to determine each prayer time based on the current user's location. This device is equipped with digital compass and Global Positioning System (GPS) where it will display the exact Qibla direction and prayer time automatically at any place in the world. This device is reliable, user friendly and accurate in determining the Qibla direction and prayer time.